Review: Eksplorasi Potensi Leguminosa Pohon sebagai Pakan Konvensional - Abdul Rouuf Hidayatullah; Fifian Cahya Rini (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Leguminous plants are plants with high protein and nutrient content, especially the protein content. Leguminous plants can grow anywhere but these plants have not been widely utilised by farmers. Some information related to leguminous plants is expected to help farmers overcome feed in the dry season. The information was obtained by reading and analysing literature and data from various research libraries that have been published in accredited journals. Tree legumes include indigofera, lamtoro, turi, gamal, and kaliandra. Indigofera plants have a crude protein content of 29.16%, while lamtoro, turi, gamal, kaliandra and Moringa are 23.8%; 31.29%; 22.6%; 25%; and 25.77% respectively. The nutrient content is supported by high productivity, where the production of indigofera, lamtoro, turi, gamal, and kaliandra can reach 4.096 tonnesBK/ha/year; 8.1 tonnes/ha/year; 2-3 tonnes/ha/harvest; 62.76 tonnes/ha/year; and 2-3 tonnes/ha/year, respectively. Despite its potential as animal feed, the plant needs further processing to reduce the anti-nutrients contained and increase its palatability so that livestock productivity increases.